The Relationship Between Cardiovascular Xerogenic Medication Intake and the Incidence of Crown/Root Restorations - Gerardo Maupome, BDS, MSc, PhD; Dawn Peters, PhD; William A. Rush, PhD; (Blackwell Synergy, 2006)
This retrospective, longitudinal cohort study quantified the strength of the association between xerogenic cardiovascular medication use and dental restorations, using the latter as a proxy measure for dental caries experience.